Efeito fungitóxico do óleo essencial de Lippia gracilis sobre Alternaria spp - Ferreira Neto, Pedro Duarte (Universidade Federal Rural do Semi-Árido, 2016)
Alternaria alternaria is causing serious problems for the export of papaya fruit (Carica papaya L.). In view of this problem it is necessary to adopt alternative control measures such as the use of essential oils. So the aim of this study was to test the effectiveness of Lippia gracilis oil in control of Alternaria spp.. The experiments were conducted in the laboratory of Phytopathology II of the Universidade Federal Rural do Semi-Árido. In the test temperature was evaluated growth of Alternaria spp. at temperatures of 20°C, 25°C, 30ºC and 35°C. The experiment was conducted in a completely randomized design in a 21x4 factorial, four temperatures and 21 isolates of Alternaria spp., With four replications. It was observed in this assay at 25 ° C gave a higher mycelial colony growth with an average of 0.66 cm. In the test the antifungal effect of Lippia gracilis oil under the growth of Alternaria spp. in vitro and in vivo, we measured the inhibitory effect of different essential oil dose Lippia gracilis (0 uL L-1250 uL L-1, 500 uL L-1 and 750 uL L-1), with still a fungicide registered to culture for control of Alternaria spp. The Sportak (750 uL L-1). The experiment was conducted in a completely randomized design in a factorial 21x5, 4 doses of essential oil of Lippia gracilis, 21 isolates of Alternaria spp. and Sportak fungicide in 4 repetitions. For in vivo experiment was also evaluated the inhibitory effect of different essential oil dose Lippia gracilis (0 uL L-1250 uL L-1, 500 uL L-1 and 750 uL L-1), with still a registered fungicide for culture to control Alternaria spp. The Sportak (750 uL L-1) in 4 repetitions. It was observed that the antifungal effect of essential oil from Lippia gracilis at doses of 500 uL L-1 and 750 uL L-1 inhibits 100% of fungal growth. In in vivo experiment, it was found that doses from 500 uL L-1 resulted in 100% inhibition of mycelial fungus growth. Concluding that the essential oil of Lippia gracilis can be used for controlling fungi, increasing the shelf-life of the papaya fruit and reducing the use of synthetic fungicides
Keywords: Mamoeiro; Alternariose; Temperatura; Controle alternativo; Inoculação; Mamoeiro; Alternariose; Temperature; Alternative control; Inoculation; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA